Le contrôle des concentrations d'entreprises Analyse comparée du test de dominance suisse, du test SIEC européen et du test SLC américain - Botteron, Valentin (sui generis Verlag, 2021)
The merger control test is being questioned in Switzerland. Many commentators are in favor of transposing the European law in this field and its SIEC test for "Significant Impediment to Effective Competition" into the Swiss Cartel Act. This study first considers the appropriateness of a legislative change as well as the choice of a possible new test. Then, in an examination of the Comco's merger control practice from 1997 to 2019, the thesis presents the Swiss test step by step and its application in statistical form. The author then compares the Swiss test with the American SLC test and the European SIEC test with the use of didactic tables and finally formulates a legislative proposal.